Perlindungan Hukum terhadap Hak Kekayaan Intelektual atas Pembajakan Film di Indonesia - Elisheva Jocelyne Tiasono; Mera Terangta Tarigan (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2024)
This research aims to analyze the legal protection of intellectual property rights (IPR) against film piracy in Indonesia using a normative juridical research method. The normative juridical research method is an approach in legal research that focuses on the analysis of legal texts and existing norms. This research is descriptive and qualitative, where the researcher gathers data from various legal sources such as laws, court decisions, legal documents, and other legal literature. This study examines the legal regulations related to IPR, especially in the context of films, as well as cases of film piracy that have occurred in Indonesia. The results of the research show that the phenomenon of digital piracy involving illegal copying of content, such as music, films, software, and others, for commercial gain without the permission of the rightful owners. Digital piracy has weakened the importance of copyright regimes in the digital era, especially due to the presence of internet technology that enables peer-to-peer file sharing, streaming media, aggregator websites, and internet service providers that facilitate the distribution of copyrighted content without permission.